The functional efficiency of mouthguards in martial sports - Rexhepi, A. M.; Brestovci, B. (Human Movement, 2013)
The aim of this study was to evaluate the influence of three different mouthguards on the airflow dynamics of oral breathing under increased ventilatory conditions at peak workload. Methods. Twenty volunteer male martial art athletes were subjected to cardio-respiratory examination on a treadmill. Four trials were performed, without a mouthguard and with a maxillary boil-and-bite mouthguard, bi-maxillary boil-and-bite mouthguard, and PlaySafe custom-made maxillary mouthguard. For each of the four tests, subjects performed an identical incremental test to determine VO2max and other respiratory values. Results. Collected data were analyzed using descriptive analyses and paired-samples t tests. The results indicated similarity in almost all measured variables when testing with the custom-made PlaySafe maxillary mouthguard to values recorded without a mouthguard, while tests performed with the maxillary and bi-maxillary boil-and-bite mouthguards showed greater differences. Conclusions. The custom-made PlaySafe maxillary and maxillary boil-and-bite mouthguards do not significantly reduce airflow dynamics of oral breathing when compared with the bi-maxillary boil-and-bite, instead, these two types of mouthguards were found to positively affect aerobic capacity.